Paroxysmal nocturnal hemoglobinuria: Pandora’s box? - Mihnea-Alexandru Găman; Iulia Ursuleac; Daniel Coriu (Journal of Mind and Medical Sciences)
Introduction. Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired non-malignant hematological disorder which affects the pluripotent hematopoietic stem cell. The cause of PNH development is the occurrence of somatic mutations in the phosphatidylinositol glycan-A gene which encodes a protein necessary for the biosynthesis of glycosylphosphatidylinositol anchors. The diagnosis of PNH requires the presence of signs of intravascular hemolysis, thrombosis, and (or) bone marrow failure. Case Report. We report the case of a 42-year-old female, diagnosed with PNH at the age of 27, whose evolution was initially characterized predominantly by hemolytic attacks and whose disease pattern evolved towards thromboembolic episodes with the advancement of age. Conclusions. Establishing the diagnosis of PNH is a difficult task and its management requires teamwork. During the evolution of the disease, a PNH patient can acquire supplementary risk factors for thrombosis, in addition to the pro-coagulant potential of the disease itself. We reported this case to remind physicians that establishing the diagnosis of PNH is troublesome, and thus it is questionable whether PNH is a rare disease or just underdiagnosed. In this context, in the clinical practice of hematologists and other physicians as well, PNH remains a veritable Pandora's box.